2023
DOI: 10.1177/09603271231155092
|View full text |Cite
|
Sign up to set email alerts
|

Azilsartan suppresses the antiapoptotic biomarker and pro-inflammatory cytokines in rat model of cisplatin-induced retinal and optic nerve toxicity

Abstract: Background The local renin-angiotensin system has been discovered in the eyes; thus, this study evaluates the Azilsartan effect in the retina and optic nerve toxicity induced by Cisplatin in vivo. Methodology Forty-eight male rats were randomly assigned into six groups of 8 animals. Group 1 was healthy control that received 0.5 mL/day of 0.5% carboxymethyl cellulose (CMC) orally (PO). Group 2 received a single dose of the 7.0 mg/kg CIS intraperitoneally with 0.5 mL/day of 0.5% CMC-PO. Groups 3 and 4 received 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
(49 reference statements)
1
1
0
Order By: Relevance
“…In this study, cisplatin-induced histological alterations in the optic nerve include inflammation and apoptosis. Previous studies have reported similar alterations (Icel et al, 2018 ; Raheem and Mohammed Ali Mahmood, 2023 ). The current cytological alterations in the optic nerve after cisplatin treatment could be attributed to endoplasmic stress and the inhibition of autophagy.…”
Section: Discussionsupporting
confidence: 73%
“…In this study, cisplatin-induced histological alterations in the optic nerve include inflammation and apoptosis. Previous studies have reported similar alterations (Icel et al, 2018 ; Raheem and Mohammed Ali Mahmood, 2023 ). The current cytological alterations in the optic nerve after cisplatin treatment could be attributed to endoplasmic stress and the inhibition of autophagy.…”
Section: Discussionsupporting
confidence: 73%
“…Azilsartan (Azil) is an angiotensin II type 1 receptor blocker (ARB) that is used as an antihypertensive drug [ 27 ]. Azil has been shown to possess anti-inflammatory, anti-oxidant and anti-apoptotic effects that are associated with neuroprotection via blocking brain angiotensin II type 1 receptors (AT1R) [ 28 31 ]. Besides, the downstream signalling pathway of renin–angiotensin–aldosterone system (RAS) has been associated with NF-kB activation [ 32 ].…”
Section: Introductionmentioning
confidence: 99%